Simulating the effects of decoupled transfer payments using the land use model ProLand - Bernd Weinmann; Jan Ole Schroers; Patrick Sheridan (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2006)
This paper describes the bio-economic land use model ProLand and presents selected results for scenarios of coupled and fully decoupled Pillar One transfer payments under the European Union's Common Agricultural Policy (CAP). The basic assumption for the model is that land users select the land use alternative from a set of agricultural and silvicultural land use systems which is expected to generate the highest possible land rent. The model is used to estimate effects of fully decoupled transfer payments on land use in a less favoured region in Hesse, Germany. The results confirm that the CAP Reform removes the distorting effects of coupled transfer payments. The extent and direction of land use changes are spatially variant. Overall, the CAP Reform will lead to increases of permanent grassland area at the cost of arable land. The total agricultural land rent generated in the region will grow substantially, mainly due to higher amounts of transfer payments. – – Dieser Beitrag stellt das bio-ökonomische Landnutzungsmodell ProLand vor und präsentiert ausgewählte Ergebnisse für Szenarien bezüglich gekoppelter und vollständig entkoppelter Transferzahlungen der Ersten Säule der Gemeinsamen Agrarpolitik (GAP) der Europäischen Union. Die Grundannahme des Modells ist, dass Landnutzer diejenige Landnutzungsalternative aus einer Menge land- und forstwirtschaftlicher Landnutzungssysteme auswählen, welche die höchstmögliche Bodenrente auf einer Entscheidungseinheit erwarten lässt. Eine Modellanwendung simuliert die Auswirkungen vollständig entkoppelter Transferzahlungen auf eine benachteiligte Region in Hessen, Deutschland. Die Ergebnisse zeigen, dass die verzerrenden Wirkungen gekoppelter Transferzahlungen durch die Reform der GAP beseitigt werden. Der Umfang und die Richtung von Landnutzungswechseln sind raumvariant. Insgesamt führt die Reform der GAP zu Zunahmen der Dauergrünlandflächen zu Lasten des Ackerlandes. Die in der Region insgesamt erwirtschaftete landwirtschaftliche Grundrente wird vor allem wegen gestiegener Transferzahlungen substanziell zunehmen (Quelle: Verlag).
Keywords: 330; EU-Agrarpolitik; Agrarreform; Agrarboden; Agrarsubvention; Bodenrente; Deutschland